Leadership in Smart Cities & Urban Innovation: The Role of Leadership in Creating a Smart City Based on Technology and Sustainability - Anastasia br Surbakti; Umroatus Soleha; Vina Rohmatul Ummah; Mochammad Isa Anshori (Cahaya Abadi Publisher, 2025)
Leadership role in realizing a sustainable and technology-based smart city. The smart city concept emphasizes the integration of information and communication technology (ICT) to improve efficiency, quality of life and sustainability in the urban environment. This study uses a literature study method by analyzing various academic and policy sources related to the implementation of smart cities in Indonesia. The research results show that transformational leadership has a crucial role in driving the success of smart cities, especially in the aspects of sustainability and human resource development. However, smart city implementation faces various challenges, such as resistance to change, limited resources, as well as data privacy and cybersecurity issues. To overcome these obstacles, effective collaboration between government, the private sector and society is very necessary. In addition, innovative and participative leadership strategies have been proven to increase the effectiveness of smart city implementation. With the right approach, smart cities can have a positive impact on the regional economy and improve the quality of public services.